Detection of Early Warning Signs in Autism Spectrum Disorders: A Systematic Review - José María Salgado-Cacho; María del Pilar Moreno-Jiménez; Yolanda de Diego-Otero (MDPI AG, 2021)
Due to the exponential increase of autism spectrum disorders' prevalence in Western countries, it is necessary to improve early detection and intervention to enhance developmental milestones. This systematic review identified the most effective screening instrument, which can be used at an early age and which identifies the maximum number of autism cases. We identified several instruments with adequate predictive properties-the Autism Parent Screen for Infants (APSI), Battelle Development Inventory, second edition (BDI-2); Brief Infant-Toddler Social and Emotional Assessment (BITSEA); First Year Inventory (FYI); Infant-Toddler Checklist/Communication and Symbolic Behavior Scales Developmental Profile (ITC/CSBS-DP); Program of Research and Studies on AUTISM (PREAUT-Grid); Checklist for Early Signs of Developmental Disorders (CESDD); Social Attention and Communication Study (SACS); and the Screening Tool for Autism in Toddlers and Young Children (STAT)-that can be applied from 12 months of age in Western countries. The ITC/CSBS-DP has been proposed for universal screening from 12 months of age onwards, complemented by the Modified Checklist for Autism in Toddlers, Revised/Revised with Follow-Up (M-CHAT-R/F), which can be used from 15 months of age onwards. This strategy could improve early detection in at-risk children within the current health system, thus allowing for early intervention.